2000
DOI: 10.1128/cmr.13.4.547
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Diseases Caused by Oral Infection

Abstract: SUMMARY Recently, it has been recognized that oral infection, especially periodontitis, may affect the course and pathogenesis of a number of systemic diseases, such as cardiovascular disease, bacterial pneumonia, diabetes mellitus, and low birth weight. The purpose of this review is to evaluate the current status of oral infections, especially periodontitis, as a causal factor for systemic diseases. Three mechanisms or pathways linking oral infections to secondary systemic effects have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
478
1
36

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 697 publications
(522 citation statements)
references
References 118 publications
7
478
1
36
Order By: Relevance
“…Several studies have reported that immunization with whole P. gingivalis cells, cell extracts, or outer membrane preparations can reduce tissue destruction caused by a P. gingivalis challenge in animal models (13)(14)(15)(16). Furthermore, immunization with whole P. gingivalis cells or sonicated cell surface extracts reduces bone loss in the rat (17) and nonhuman primate (18) Recently, it has been recognized that oral infections, especially periodontitis, may affect the course and pathogenesis of several systemic diseases, such as cardiovascular disease, bacterial pneumonia, diabetes mellitus, and low birth weight (19). Although the importance of systemic diseases caused by periodontitis has been recognized by the dental profession, the general public still believes that periodontal diseases do not possess the potential to affect lethal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that immunization with whole P. gingivalis cells, cell extracts, or outer membrane preparations can reduce tissue destruction caused by a P. gingivalis challenge in animal models (13)(14)(15)(16). Furthermore, immunization with whole P. gingivalis cells or sonicated cell surface extracts reduces bone loss in the rat (17) and nonhuman primate (18) Recently, it has been recognized that oral infections, especially periodontitis, may affect the course and pathogenesis of several systemic diseases, such as cardiovascular disease, bacterial pneumonia, diabetes mellitus, and low birth weight (19). Although the importance of systemic diseases caused by periodontitis has been recognized by the dental profession, the general public still believes that periodontal diseases do not possess the potential to affect lethal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The studies reviewed above and several others have suggested that oral bacteria may cause respiratory diseases when (i) oral bacteria or respiratory pathogens from oral reservoirs are aspirated into the lower respiratory tract, (ii) salivary enzymes released during chronic periodontal disease or smoking modify the oral mucosa and lead to increased adhesion by respiratory pathogens, and/or (iii) circulating pro‐inflammatory cytokines released as a consequence of periodontal inflammation modify the respiratory mucosa (Li et al . ; Paju & Scannapieco, ).…”
Section: The Oral Microbial Ecosystem – Real Estate and Habitatsmentioning
confidence: 99%
“…The most common method of controlling plaque build‐up is through mechanical removal with a toothbrush. Plaque build‐up has been associated with systemic infections , cardiovascular disease , adverse pregnancy outcomes , respiratory diseases and aspiration pneumonia .…”
Section: Introductionmentioning
confidence: 99%